The impact of integrase inhibitor-based regimens on markers of inflammation among HIV naïve patients. (February 2020) - Quiros-Roldan, Eugenia; Castelli, Francesco; Bonito, Andrea; Vezzoli, Marika; Calza, Stefano; Biasiotto, Giorgio; Zanella, Isabella; ,
Highlights: Chronic immune activation and inflammation persist in cART treated HIV patients. Immune activation and inflammation are predictors of mortality in HIV patients. Distinct cART regimens may have different impact on inflammation/immunoactivation. Abstract: The use of combination anti-retroviral therapy (cART) correlates with longer and healthier life and with nearly normal life expectancy in people living with HIV. However, cART does not completely restore health. Chronic immune activation and inflammation persist in treated patients and have been described as predictors for clinical events and mortality in HIV-infected patients. Limited information is available on the impact of the various cART regimens on inflammation/immunoactivation. The aim of this work was to explore the impact of elvitegravir, dolutegravir, raltegravir (integrase strand transfer inhibitors, INSTIs) and atazanavir (protease inhibitor, PI) on several soluble markers of immune activation and inflammation during the first year of effective combination anti-retroviral therapy (cART). We conducted an observational retrospective cohort study in HIV-infected cART-naïve patients who initiated an INSTI or atazanavir regimen between March 2015 and February 2016 and a serum sample was available at baseline, 6 and 12 months after initiation. We compared the trend of D-Dimer, TNF- α, IL-2, IL-6, IL-7, IL-10, CCL4/MIP1-β, CCL5/RANTES, s-CD14, s-CD163, hs-CRP levels among the 4 arms of treatment. Percentage of variation from baseline was also measured for all markers. A total of 36 patients were included. We observed heterogeneous modifications in inflammation markers among arms. In particular, we noted that EVG have significant negative effect on s-CD14, hs-CRP, IL-6 and D-Dimer in respect to other INSTIs and this different effect occurs mainly during the first 6 months of cART. IL-7 values increased in the three arms with INSTIs (significantly only in EGV, 159.8%, p = 0.0003) and decreased significantly in patients on PI (−48.96%; p = 0.04) over the period. In conclusion, our results provide further data on changes of inflammatory marker levels, especially for the new INSTIs. Our data show that among INSTIs, EVG seems to have a worse impact on inflammation.